2013
DOI: 10.7705/biomedica.v33i3.1441
|View full text |Cite
|
Sign up to set email alerts
|

Correlación de la t(9;22), t(12;21) e hiperdiploidia de ADN, con el inmunofenotipo, y la tasa proliferativa de células B neoplásicas de pacientes pediátricos con leucemia linfoide aguda de precursores B

Abstract: Instituciones donde se llevó a cabo el trabajo: Fundación Santa Fe de Bogotá, Fundación Hospital de la Misericordia y Pontificia Universidad Javeriana.Introducción. Del 60 al 80 % de los pacientes con leucemia linfoblástica aguda de precursores B presentan alteraciones genéticas que influyen en el pronóstico de la enfermedad y en la biología del tumor. Objetivo. Analizar distintas alteraciones genéticas en leucemia linfoblástica aguda de precursores B en niños, y su relación con el inmunofenotipo y con la tasa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 42 publications
1
3
0
Order By: Relevance
“…Similar to what has been reported in the literature, comparative immunophenotype analysis between B-ALL cases and their normal counterpart, revealed high heterogeneity in the expression of the different markers suggesting the existence of leukemia associated phenotypes (LAP) [ 11 , 26 ] in our cohort of patients. Leukemic lymphoblast cells were characterized by over-expression (median fluorescence channel) of CD34 and CD10 immaturity markers, B lineage markers such as CD19 and CD24, the lymphocyte common antigen CD45 and aberrant expression of myeloid lineage associated marker CD66.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…Similar to what has been reported in the literature, comparative immunophenotype analysis between B-ALL cases and their normal counterpart, revealed high heterogeneity in the expression of the different markers suggesting the existence of leukemia associated phenotypes (LAP) [ 11 , 26 ] in our cohort of patients. Leukemic lymphoblast cells were characterized by over-expression (median fluorescence channel) of CD34 and CD10 immaturity markers, B lineage markers such as CD19 and CD24, the lymphocyte common antigen CD45 and aberrant expression of myeloid lineage associated marker CD66.…”
Section: Resultssupporting
confidence: 88%
“…The presence of CD38 (>30%) is associated with worse prognosis in mature B-cell tumors like B-chronic lymphoid leukemia and in hairy cell leukemia, T and NK lymphoma [ 41 , 42 ]. However, our work and another report on hematopoietic tumors of B-ALL pediatric Colombian patients [ 26 ], describes an under-expression of CD38 in the group of patients with poor prognosis. Similar to our findings, Quijano et al [ 26 ] reported that higher FSC (larger size) was associated with patients with good prognostic.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations